2020
DOI: 10.1111/1758-2229.12870
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DNA builds and interacts with vibrio polysaccharide in the biofilm matrix formed by Vibrio cholerae

Abstract: Summary Vibrio cholerae form biofilm, which is essential for their survival under harsh environmental conditions. The eDNA produced during biofilm formation and interaction with other components like vibrio polysaccharide is less studied in Vibrio cholerae despite its importance in biofilm structure and stability. In this study, we selected two strains of V. cholerae, which produced sufficient extracellular DNA in the biofilm, for characterization and studied its interaction with vibrio polysaccharide. Our dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…T6SS-mediated eDNA release has previously been shown to facilitate horizontal gene transfer in V. cholerae grown on chitin, implying that strain interfaces where T6SS killing occurs have the potential to be evolutionary hotbeds ( 44 , 54 ). eDNA has additionally been shown to interact with VPS in V. cholerae biofilms ( 55 ), suggesting that eDNA release via T6SS could also play a structural role within biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…T6SS-mediated eDNA release has previously been shown to facilitate horizontal gene transfer in V. cholerae grown on chitin, implying that strain interfaces where T6SS killing occurs have the potential to be evolutionary hotbeds ( 44 , 54 ). eDNA has additionally been shown to interact with VPS in V. cholerae biofilms ( 55 ), suggesting that eDNA release via T6SS could also play a structural role within biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…The biofilm 3D structure of Bacillus subtilis showed that polysaccharides could interconnect with eDNA in the early stage of biofilm formation, and was mainly the structure material of the mature biofilm (Peng et al, 2019). Kanampalliwar and Singh (2020) reported that the interaction between eDNA and polysaccharides could contribute to the biofilm integrity of Vibrio cholerae. In this research, the S-EPS 2 could bond on the anion exchange column DEAE-Sepharose Fast Flow during the S-EPS purified process and S-EPS 2-1 was the main component of S-EPS 2, indicating that S-EPS 2-1 might have the negative charge (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In this same sense, the copper (I) complex could affect eDNA, which is an important part of EPS and plays a key role in the initial adhesion and structural stability of the biofilm in Gram-negative and -positive bacteria [44]. Studies carried out in Vibrio cholerae have shown that eDNA is able to interact with the exopolysaccharides in the EPS, improving strength and stability of the biofilm and contributing to antimicrobial resistance [45]. In this respect, in analyses carried out in P. aeruginosa with copper (II) complexes, it has been shown that they are capable of increasing the antibiofilm effect by inhibiting the amount of biofilm eDNA [46].…”
Section: Discussionmentioning
confidence: 99%